Approaching Two‐Dimensional Copolymers: Photoirradiation of Anthracene‐ and Diaza‐Anthracene‐Bearing Monomers in Langmuir Monolayers. Issue 2 (5th December 2014) - Payamyar, Payam; Servalli, Marco; Hungerland, Tim; Schütz, Andri P.; Zheng, Zhikun; Borgschulte, Andreas; Schlüter, A. Dieter; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> By using structurally similar amphiphilic monomers, it is shown that compressed monolayers of varying amounts of such monomers at the air/water interface can be converted by photoirradiation into the corresponding covalently connected monolayer sheets. Since one of the monomers carries three anthracene units and the other three 1, 8‐diaza‐anthracene units, the growth reaction is proposed to take place through photochemically achieved [4+4]‐cycloaddition between pairs of these units that are co‐facially (face‐to‐face) arranged, to furnish the corresponding covalent dimers. While evidence for both homodimers is amply available, the existence of the heterodimer needs to be established with the help of a model reaction to support the conceptual aspect of this work, copolymerization in two dimensions. The sheet copolymers exhibit substantial robustness in that they can be spanned over 20 × 20 μm2‐sized holes without rupturing under their own weight. X‐ray photoelectron spectroscopy (XPS) studies reveal that the monomers are incorporated into the sheet copolymers according to feed. These results establish existence of the first covalent sheet copolymer, which is considered a step ahead towards novel 2D materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>